GREEN ECONOMIC: ADOPTION OF NON-CASH PAYMENT SYSTEMS IN BUSINESS TRANSACTIONS - Fauziah, Fenty; Adhadianawaty, Sri Aisyiyati Sitti Noor; Fitriansyah, Fitriansyah; Nurfadillah, Mursidah; Zien, Nur Hanisfatin Rushami (International Journal of Cultural and Social Science, 2025)
Technological developments encourage MSMEs to adopt non-cash payments to improve competitiveness and consumer experience. This study analyzes the influence of technological, organizational, and environmental factors on the adoption of non-cash payment systems in MSMEs in Samarinda City. The research method used a sample of 130 MSME actors selected by random sampling. The results of the analysis show that all three factors have a positive effect on the adoption of non-cash payments. This finding emphasizes the importance of technological support, internal readiness of MSMEs, and external pressure in encouraging the transition to a cashless system. The practical implication is that MSMEs need to adapt to digital payment systems to improve business efficiency and support sustainability (paperless). Theoretically, this study strengthens the understanding of the determinants of digital innovation adoption in the MSME sector, while providing recommendations for business actors, government, and fintech providers in expanding the use of non-cash payments.